The muscular monk : Vivekananda, sports and physical culture in colonial Bengal - Chatterjee, Amitava; Naha, Souvik (2014)
Swami Vivekananda's thoughts are a complex and multidimensional interplay of India's ancient and medieval past and his 19th century milieu. He was an ardent advocate of masculinity and sports. This article discusses the influential contributions to theories of masculinity which provide a framework within which Vivekananda's physical activities and gendered notions can be situated. His belief that football is not insignificant reveals his concerns for the development of manliness among the so-called effeminate Bengalis. He himself practised a number of colonial sports and expressed profound interest in golf though these sports were not seen as a form of leisure. The lessons of physical culture not only strengthened his body but empowered his mind against inequality and perils. Vivekananda appeals to the Hindu sources for his construction of the body and mind of the spiritual aspirant as a site delimited and shielded. - Reproduced.
Keywords: Vivekananda, Swami